The Application of Utility in Indonesia Based on the Principles of Utilitarianism - Arlene Agustina; Livia Clarista (Universitas Lampung, 2018)
Utilitarianism is a principle claiming that the greatest amount of happiness is an end that should exclusively guide all actions of both government and individuals. The fact that people value happiness is considered to be morally right. This principle is pursued by Jeremy Bentham, who believes that the two sovereigns in life are pleasure and pain. It holds an important aspect in law enforcement since it sees what will benefit people the most as the main discussion. Even though there is still some party that opposes or overlooks this view, especially in Indonesia, writers believe that utility is the powerful principle that cannot be set aside. It is needed to be seen as an important aspect on law enforcement so that it can bring happiness and satisfaction to the society. Keywords: Utility, Happiness, Moral, Utilitarianism, Society.